2006
DOI: 10.1007/s00246-006-1082-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the EGF-CFC Gene Cryptic Are an Infrequent Cause of Congenital Heart Disease

Abstract: Cryptic (CFC1), a member of the epidermal growth factor-Cripto/FRL-1/Cryptic (EGF-CFC) gene family, is involved in the evolutionarily conserved establishment of left-right lateral asymmetry. Inactivation of Cfc1 in mice results in laterality defects and complex cardiac malformations. Similarly, mutations in the human CFC1 gene have been identified in patients with heterotaxy syndrome. The cardiac defects in humans resemble those in mice lacking Cfc1. We postulated that some patients with isolated cardiac malfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…NODAL, a member of transforming growth factor‐beta (TGFβ) superfamily of developmental regulators, is part of the NODAL signal transduction pathway, which regulates the establishment of the LR axis. Mutations have also been found in other components of the NODAL signal transduction pathway, including the GDF1 (26), LEFTY2 (27), ACVR2B (28), CFC1 (29, 30), FOXH1 (10) and TDGF1 (10) genes (Fig. 1).…”
Section: Ligands and Receptorsmentioning
confidence: 99%
“…NODAL, a member of transforming growth factor‐beta (TGFβ) superfamily of developmental regulators, is part of the NODAL signal transduction pathway, which regulates the establishment of the LR axis. Mutations have also been found in other components of the NODAL signal transduction pathway, including the GDF1 (26), LEFTY2 (27), ACVR2B (28), CFC1 (29, 30), FOXH1 (10) and TDGF1 (10) genes (Fig. 1).…”
Section: Ligands and Receptorsmentioning
confidence: 99%
“…Finally, we note that Ozcelick et al also detected the A145T variant, both in normal controls and in patients with cardiac malformations, and concluded that this variant was unlikely to contribute to disease. 30 However, because the distinction between common polymorphisms and disease variant alleles is empiric and given our own documented examples of functionally abnormal common polymorphisms (e.g., (P75P) R78W above), a definitive assignment cannot be made without further studies. For example, we observed a patient that has the hypomorphic common polymorphism (P75P) R78W in CFC1 as well as a unique FOXH1 allele (V112M, described below) with diminished function, suggesting that genetic interactions might occur in some individuals with variations in more than one gene (see Figures 3-5).…”
Section: Sequence Variation In the Egf-cfc Proteinsmentioning
confidence: 99%
“…To this homogenous ASDII patient cohort we added a group of 95 individuals with different congenital septal defects (60 ASDII, 22 perimembranous VSD, and 13 AVSD) and concomitant minor cardiac malformations (Aortic coarctation = CoA, persistent ductus arteriosus = PDA or partial anomalous venous return = PAPVR). These patients were included as a subgroup in a candidate gene approach reported previously [Ozcelik et al, 2006]. All patients were attending the Department for Congenital Heart Disease, German Heart Institute Berlin (GHIB).…”
Section: Genetic Variants Identified In 205 Probands With Congenital mentioning
confidence: 99%